Comportamiento agronómico y de rendimiento bajo distanciamientos de siembra en Eryngium foetidum L. “sacha culantro”, en Zungarococha-Loreto.2021 - Perez Hidalgo, Marck Paul (2022)
The Thesis "Agronomic behavior and yield under planting distances in Eryngium foetidum L. "sacha culantro", in Zungarococha-Loreto.2021", was carried out in the Workshop of Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located, south of the city of Iquitos, Loreto Region. The type of research was experimental, prospective, experimental, descriptive, with one independent variable (Planting distances) and seven dependent variables (Plant height, Plant diameter, root length, number of leaves/plant, weight of leaves/plant, total weight of plant and weight of plants/ha). The main objective of the research work was to determine the behavior of the agronomic and yield components under planting distances of Eryngium foetidum L. "sacha culantro". The Statistical Design that was handled was the Completely Random Block Design, with four treatments and four repetitions. Each experimental unit consisted of 4 rows, 12 floors/row (T1); 10 floors/row (T2); 8 floors/row (T3) and 7 floors/row (T4) and the sampling unit consisted of four plants/experimental unit. With the results obtained at the end of the experiment, the following conclusions were reached: Planting distancing influences agronomic and yield behavior in Eryngium foetidum L." sacha culantro".the T4 Treatment (0.35 m x 0.20 m), obtained the best results in, plant diameter, root length, number of leaves/plant, weight of leaves/plant, and total weight of the plant;; the T3 Treatment (0.30 m x 0.20 m), presented the best average value of plant weight yield / ha with 16,000 Kg / ha and also obtained the best Benefit-Cost ratio, with S / .49,379.00.